Organizational Structure of Bank Indonesia: Influences of Contingency Factors on Organizational Structure of Monetary Sector of Bank Indonesia - , Cut Arifah, SE ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study deals with influences of contingency factors on organizational structure of monetary sector of Bank Indonesia. The researcher believes that there is no one best organizational structure. Every organization has its own condition which can influence the structure for the organization itself. Therefore, organization needs to identify these factors and determine which of these factors has the most influence in order to develop a suitable structure for the organization. The researcher took Bank Indonesia and focus on monetary sector as object of research because among other sectors this sector produce and perform the main products of Bank Indonesia-that is monetary policy and monetary policy implementation. The researcher analyzed five factors which are believed have high influences on how organization should consider in developing a suitable organizational structure. These factors were: size, technology, environment, strategy, and power. Objective of this study are to identify causes of current problems which occur along the business process of monetary sector, and related the problem to how each contingency factor affected organizational structure of monetary sector. Focus of this study is on coordinating mechanism among units involves in producing main outputs of monetary sector. The researcher found that some problems along the business process of monetary sector were related to the organizational structure of monetary sector. It was also found that one or some contingency factors have affected on how coordinating mechanism should be developed among units or business process players. These findings illustrated that the influences of contingency factors has not been well considered on current organizational structure of monetary sector.